Évaluation économique des programmes de remplacement de la main d’oeuvre expatriée dans les pays en voie de développement : étude du cas de la Côte-d’Ivoire - Monson, Terry; Pursell, Garry (L'Actualité économique)

(untitled) (HEC Montréal, 1977)
AbstractThis study addresses several problems of educational policy posed by the replacement of highly skilled expatriates in the Ivory Coast's labor force. Conceptualizing expatriate replacement as an import-substitution activity in which Ivorian labor substitutes for previously imported labor services, the authors apply a modified Domestic Resource Cost (DRC) analysis to evaluate Ivorian secondary and university educational programs necessary to train the local labor.This methodology, along with more conventional cost-benefit approach, confirms that education is economically desirable in the Ivory Coast and that resource allocation to the upper secondary level is especially warranted. Lower secondary education is useful in so far as it performs a conduit function for higher levels of training. The importance of university education will probably increase as the occupational-educational structure is upgraded through technological development. Finally, consideration should be given to instituting a system of tuition charges in order to equate social and private rates of return in upper secondary and university education.